ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Asri Vega Safitri, 11.05.52.0185; ., Wardjono (Students Journal of Accounting and Banking, 2015)
This research aims to understand the influence of Debt To Equity Ratio, Price To Book Value, Earning Per Share, Total Assets Turnover and Size to return the company shares categories including Real Estate and Property registered in Indonesia stock exchange. The population was all companies Real Estate and Property in the Indonesia stock exchange. The sample collection technique used is purposive sampling. The analysis used in this research are multiple linear regression model. The result showed that the coefficients determination in this research is the value of adjusted R square worth 12,1 %. While for F-test statistic shows that, between Debt To Equity Ratio (DER), Price to Book Value (PBV), Earning Per Share (EPS), Total Asset Turnover (TATO) and Size jointly impact on stock return. And the results of the testing of hypotheses partial evaluation shows that there is a positive significant influence between Price To Book Value (PBV) against stock return. While for Earning Per Share (EPS) and Size there is a positive not significant against stock return. Debt To Equity Ratio (DER) and Total Asset Turnover (TATO) shows that there are negative not significant impact on stock return.Keywords: Debt to Equity Ratio, Price to Book Value, Earning Per Share, Total Asset Turnover, Size and Stock Return